Current practices of peripheral intravenous catheter fixation in pediatric patients and factors influencing pediatric nurses’ knowledge, attitude and practice concerning peripheral intravenous catheter fixation: a cross-sectional study - Li-Sha Huang (BMC, 2021)
Abstract Background Peripheral intravenous catheters (PIVCs) are the most widely used intravenous treatment tools for hospitalized patients. Compared to adult patients, PIVC fixation issues are more likely to occur in pediatric patients and can be more complex. However, research on PIVC fixation in pediatric patients is rare. This study aimed to investigate the pass rate for PIVC fixation in pediatric patients and the factors that influence pediatric nurses’ knowledge, attitude, and practice (KAP) concerning PIVC fixation. Methods An on-site investigation using a self-designed PIVC fixation standard inspection checklist for first insertion and routine maintenance in pediatric patients and a follow-up questionnaire survey investigating pediatric nurses’ KAP concerning PIVC fixation was conducted in a hospital in China between November 1 and December 31, 2019. Data were analyzed using SPSS 21.0. Results The pass rate for PIVC fixation in pediatric patients was 52.02%. The pediatric nurses’ knowledge, attitude and practice scores on PIVC fixation were 7.2 ± 1.36, 28.03 ± 2.42, and 31.73 ± 2.94, respectively. The multivariate linear regression analysis results show that department (where nurses are working in) and job position are the factors that influence knowledge score (B > 0, P < 0.05); department is also a factor that influences attitude score (B > 0, P < 0.05); and department and nursing hierarchy are the factors that influence practice score (B > 0, P < 0.05). Conclusion PIVC fixation in pediatric patients is affected by multiple factors. The level of pediatric nurses’ KAP on PIVC fixation needs to be improved. It is suggested that guidelines for PIVC fixation in pediatric patients be formulated and that training on PIVC fixation in pediatric patients be provided for pediatric nurses in an effort to raise the pass rate in terms of PIVC fixation in pediatric patients.